C-H center dot center dot center dot N hydrogen bonds mediated solid state structures of 2,2 `-bis (4-pyridylsulfanylmethyl)-1,1 `-biphenyl and 9-(4-pyridylsulfanyl)phenanthrene - Upadhye, Ketaki; PrakashaReddy, J.; Pedireddi, V. R. (Journal of Molecular Structure, 2009)
Solid state structure elucidation of sulfanyl ligands, 2,2'-bis(4-pyridylsulfany[methyl)-1,1'-biphenyl, L(1) and 9-(4-pyridylsulfanyl)plienanthrene, L(2) are reported. In the structures L(1) and L(2), the molecules are self-assembled through C-H center dot center dot center dot N hydrogen bonds, yielding ensembles of cyclic and helical networks. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: hydrogen bonds; noncovalent interactions; Supramolecular assemblies

Synergistic effects and correlating polarity parameters in binary mixtures of ionic liquids - Beniwal, Vijay; Kumar, Anil (Chemphyschem, 2015)
Understanding how a chemical reaction proceeds in solution requires precise knowledge of solute-solvent interactions. Certain issues involved in ionic liquid binary mixtures are still not clearly understood, including: 1) the effects of hydrogen-bond-acceptor basicity () of solvents on the synergistic effects found in ionic liquid-alcohol mixtures, 2) the interrelation between the polarity parameters in binary mixtures, and 3) the application of a model for the description of normalised electronic transition energy for all the binary mixtures. Here, a detailed analysis of polarity parameters in both hydrophilic and hydrophobic ionic liquids has been carried out. A three-parameter model developed by Roses et al. [J. Chem. Soc. Perkin Trans. 2 1997, 13411348] was found to be applicable to all the binary mixtures, and synergistic effects are generated as a result of high values of alcohols compared with those of the ionic liquids. A strong correlation was observed in the values and hydrophobicities of pure ionic liquids, suggesting that values can play a role in describing synergism.
Keywords: green chemistry; ionic liquids; liquids; noncovalent interactions; solvent effects

Engineering molecular topology: A pseudopeptidic macrocyclic figure-eight motif - Sharma, Sakshi; Thorat, Shridhar H.; Gonnade, Rajesh G.; Jasinski, Jerry P.; Butcher, Ray; Haridas, V. (European Journal of Organic Chemistry, 2017)
We herein present a rational-design strategy for the synthesis of molecules with figure-eight topology. The design concept is based on the incorporation of turn units in the back-bone of the macrocycle. The molecular structures and the folding are studied by X-ray crystallography and NMR, FT-IR, and CD spectroscopy.
Keywords: Macrocycles; noncovalent interactions; Pi interactions; topology; X-ray diffraction

"Weak" C-H•••S interaction drives enantioselectivity in cinchona alkaloid complex catalyzed thiocyanation - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-An Asian Journal, 2023)
The great success of asymmetric organocatalysis has made it one of the most important advancements made in chemistry in the past two decades. A significant achievement in this context is the asymmetric organocatalysis of the thiocyanation reaction. In the current study, computational studies with density functional theory have been done in order to understand an interesting experimental finding: the reversal of enantioselectivity from R to S when the electrophile is changed from beta-keto ester to oxindole for the thiocyanation reaction with the cinchona alkaloid complex catalyst. The calculations reveal an unusual fact - the principal reason for the reversal is the presence of the C-H center dot center dot center dot S noncovalent interaction, which is present only in the major transition states in each of the two nucleophile cases. Only recently has it been realized that the supposedly weak C-H center dot center dot center dot S noncovalent interaction has the properties of a hydrogen bond, and the fact that this interaction is the cause of enantioselectivity has relevance, because of the large number of asymmetric transformations involving the sulphur heteroatom.
Keywords: Density functional calculations; Enantioselectivity; noncovalent interactions; organocatalysis; reaction mechanisms

Taming XeO3 with aza-crowns: computational studies into σ-hole mediated host-guest interactions - Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2024)
Various aza-crowns with different sizes and substituents have been explored computationally as potential hosts for stabilizing the explosive guest xenon trioxide (XeO3) through sigma-hole-mediated aerogen bonding interactions. Interestingly, aza-crowns demonstrate superior binding towards XeO3 compared to their oxygen and thio counterparts. However, unlike the latter cases, where the binding was found to be increasingly favorable with the increase in the size of the crowns, aza-crowns exhibit a variable size preference for XeO3, peaking with aza-15-crown-5, and reducing thereafter with increase in crown size.
Keywords: aza-crowns; host-guest systems; noncovalent interactions; sigma (sigma) hole; Xenon